Water relations of sour cherries (minireview) - Nemeskéri, E. (International Journal of Horticultural Science, 2007)
Recently, the sour cherries as food resources become more important for health preservation and so the modernization of growing technology in sour cherry production will be timely. The global warming and inadequate distribution of precipitation result a decrease in the alternancy of sour cherry production, as well. Sour cherries rather adapted to survival of drought than sweet cherry trees therefore a few studies performed to explore the water requirement of sour cherry varieties. The rootstocks, the type of soils in plantation and the water balance influence the water management of sour cherries. In orchards, in particular first year plantation, use of various row covering contribute to preservation of the natural water pool of soil and affect on the tree vigor, yield and fruit quality. Wide-spread application of integrated fruit growing technology and climate changes the researches are pointed to develop efficient irrigation technology based on transpiration yield model. The crop model based on use of meteorological data was developed for cherry orchards in order to predict transpiration of trees, dry matter production and fruit yield. The linear relationship between dry matter accumulation and transpiration was verified for sour cherry trees. Other models essay to asses the effects of climate changes on crop production. Importance of economical production and fruit quality such as ingredients of raw materials and food increases in intensive sour cherry orchards used by irrigation techniques. Because of climate changes it should more pay attention to research concerning on the stress physiological response of sour cherry varieties and post-harvest fruit quality.